Life-cycle greenhouse gas emission and energy use of bioethanol produced from corn stover in China: Current perspectives and future prospectives. (15th November 2016) - Zhao, Lili; Ou, Xunmin; Chang, Shiyan
Abstract: In this study, a life cycle analysis (LCA) of bioethanol production from corn stover is carried out under Chinese context. Three scenarios were developed and assessed based on current and future technology levels of the ethanol conversion process. Well-to-pump (WTP) and well-to-wheels (WTW) results are presented in this paper via functional units of 1 MJ of ethanol produced, 1 MJ of E100 produced and used, and 1 km of distance driven by a light-duty vehicle on E10 fuel, respectively. It was calculated that for 1 MJ of E100, the WTW Greenhouse gas (GHG) emission reduction relative to gasoline reaches 52%–55%, and the savings of fossil fuel and petroleum fuel reach 72%–76% and 74%–85%, respectively. For 1 MJ of ethanol produced, GHG emissions occurred in ethanol conversion process account for 51%–55%, and the contribution of chemical inputs reaches 36%–37% of the total life cycle GHG emissions. Furthermore, the life cycle results were found to be highly sensitive to allocation methods. Highlights: The study is focused on 2 G bioethanol derived from corn stover in Chinese context. LCA is based on both current and future technology levels for ethanol conversion. The life cycle GHG emission reduction of E100 relative to gasoline reaches 52%–55%. Contributions of chemicals account for 36%–37% of life cycle GHG emissions. E100 saves 74%–85% of petroleum fuel during its life cycle production and use.